The impact of boarding school on student development in primary and secondary schools: a meta-analysis - Zhong, Zhiyong; Feng, Yang; Xu, Yongqi (Frontiers in Psychology, 2024)
As a long-established model of schooling, the boarding system is commonly practiced in countries around the world. Numerous scholars have conducted a great deal of research on the relationship between the boarding school and student development, but the results of the research are quite divergent. In order to clarify the real effects of boarding school on students’ development, this study used meta-analysis to quantify 49 (91 effect sizes) experimental or quasi-experimental studies on related topics at home and abroad. The results find that: (1) Overall, boarding school has no significant predictive effect on student development, with a combined effect size of 0.002 (p > 0.05); (2) Specifically, boarding school has a significant positive predictive effect on students’ cognitive development (g = 0.248, p < 0.001), a significant negative predictive effect on students’ affective and attitudinal development (g = −0.159, p < 0.05), and no significant predictive effect on students’ behavioral development (g = −0.115, p > 0.05) and physical development (g = −0.038, p > 0.05); (3) The relationship between the two is moderated by the school stage and the type of boarding school, but not by the instruments; (4) Compared with primary school students, senior high school students and urban boarding students, the negative predictive effect of boarding system on junior middle school students and rural boarding students is more significant. In addition, there are some limitations in the study, such as the limited number of moderator variables included, the results of the study are easily affected by the quality of the included literature, and the dimensionality of the core variable “student development” is not comprehensive enough. In the future, further validation should be conducted through in-depth longitudinal or experimental studies.